Epidemiological profile of patients who died from tuberculosis in Piauí between 2016 and 2020 (Research, Society and Development, 2021)
Tuberculosis is caused by Mycobacterium tuberculosis, which most frequently affects the lungs, being transmitted from person to person through the air. In this sense, about a quarter of the world population has tuberculosis infection and pathologies are associated with mortality from the disease. This research aimed to outline an epidemiological profile of patients who died from tuberculosis in Piauí between 2016 and 2020. The epidemiological data of patients who died from tuberculosis were sourced from the SUS Informatics Department (DATASUS). In the data observed, the year 2018 was the year with the highest number of cases, with 842, on the other hand, the year 2016 was the year with the highest percentage of deaths compared to cases present in the year, with a total of 10.2 % of infections leading to death. Among those observed between the years 2016-2020, smoking was the risk factor most associated with tuberculosis. When compared to other diseases such as infectious, dengue and HIV, tuberculosis was the second leading cause, with its highest percentage of 36.1% in 2016. Therefore, it is essential to develop awareness-raising actions and permanent qualification of professionals involved in tuberculosis control actions, as well as improving the case notification system, with more systematic audits at the state level, which can measure and generate improvements in the control of public health problems.